1982
DOI: 10.21273/jashs.107.6.1078
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Trends of Calcium, Magnesium, and Potassium Fractions in Apple Leaf and Fruit Tissues1

Abstract: Leaf and fruit tissues of apple (Malus domestica Borkh.) were sequentially fractionated using hot water, sodium nitrate, acetic acid, and hydrochloric acid to extract Ca, Mg, and K in various forms. Water-soluble and sodium nitrate-exchangeable Ca were considered physiologically active forms and increased from 50 to 84% of the total Ca in fruit during the season and decreased from 57 to 45% in leaves. About 90% of the Mg and K concentrations in fruit were physiologically active. Physiologically active forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…All the minerals present in the apple peel and pulp affect physiological functions in plant metabolism, with some elements present in significant amounts while others play a minor role. As mentioned earlier, potassium is most abundant in fruit tissues (peel, pulp), and this organ is a strong sink for K, while nitrogen, as a building block, links the uptake of all other elements in fruit tissues [131][132][133][134]. It is confirmed that the apple peel has a slightly higher to several times higher content of many bioactive compounds compared to the fruit pulp.…”
Section: Apple Fruit Mineral Content and Its Qualitymentioning
confidence: 80%
“…All the minerals present in the apple peel and pulp affect physiological functions in plant metabolism, with some elements present in significant amounts while others play a minor role. As mentioned earlier, potassium is most abundant in fruit tissues (peel, pulp), and this organ is a strong sink for K, while nitrogen, as a building block, links the uptake of all other elements in fruit tissues [131][132][133][134]. It is confirmed that the apple peel has a slightly higher to several times higher content of many bioactive compounds compared to the fruit pulp.…”
Section: Apple Fruit Mineral Content and Its Qualitymentioning
confidence: 80%